Local injection of stem cell factor (SCF) improves myocardial homing of systemically delivered c-kit + bone marrow-derived stem cells - Lutz, Matthias; Rosenberg, Mark; Kießling, Fabian; Eckstein, Volker; Heger, Thomas; Krebs-Haupenthal, Jutta; Ho, Anthony Dick; Katus, Hugo; Frey, Norbert (Cardiovascular research, 2008)
Recent studies have shown that stem cell therapy may alleviate the detrimental effects of myocardial infarction. Yet, most of these reports observed only modest effects on cardiac function, suggesting that there still is need for improvement before widespread clinical use. One potential approach would be to increase migration of stem cells to the heart. We therefore tested whether local administration of stem cell factor (SCF) improves myocardial homing of intravenously infused lin-/c-kit+ stem cells after myocardial infarction.Myocardial infarction was induced in mice via ligation of the left anterior descending artery and 2.5 µg of SCF were injected into the peri-infarct zone. Sham-operated mice and animals with intramyocardial injection of phosphate-buffered saline (PBS) served as controls. Twenty-four hours after myocardial infarction, lin-/c-kit+ stem cells were separated from murine bone marrow by magnetic cell sorting, labelled with the green fluorescent cell tracker CFDA or 111Indium, and subsequently 750 000 labelled cells were systemically infused via the tail vein. Another 24 or 72 h later, respectively (i.e. 48 and 96 h after myocardial infarction), hearts were removed and analysed for myocardial homing of stem cells. Green fluorescent stem cells were exclusively detected in the peri-infarct zone of animals having prior SCF treatment. Radioactive measurements revealed that an intramyocardial SCF injection significantly amplified myocardial homing of lin-/c-kit+ stem cells compared to animals with PBS injections (3.58 ± 0.53 vs. 2.28 ± 0.23 cpm/mg/106cpm, +60%, P < 0.05) and sham-operated mice without myocardial infarction (3.58 ± 0.53 vs. 1.95 ± 0.22 cpm/mg/106cpm, +85%, P < 0.01). Similar results were obtained 72 h after stem cell injection.We demonstrate that intramyocardial administration of SCF sustainably directs more lin-/c-kit+ stem cells to the heart. Future studies will have to show whether higher levels of myocardial SCF (i.e. by virus-mediated gene transfer) can further improve homing of systemically delivered c-kit+ stem cells and thus favourably influence cardiac remodelling following myocardial infarction.